1999
DOI: 10.1021/ie990209p
|View full text |Cite
|
Sign up to set email alerts
|

Olefin/Paraffin Separation through Carbonized Membranes Derived from an Asymmetric Polyimide Hollow Fiber Membrane

Abstract: Carbonized hollow fiber membranes were prepared by pyrolyzing an asymmetric hollow fiber membrane of a polyimide from 3,3‘,4,4‘-biphenyltetracarboxylic dianhydride and aromatic diamines at temperatures of 500−700 °C under a nitrogen stream. The precursor membrane was treated in air at 400 °C for 0.5 h before the pyrolysis. This pretreatment was effective for improvement of gas permeance of the carbonized membranes. The carbonized membranes had an asymmetric structure with a skin layer of around 200 nm in thick… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
78
0
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(82 citation statements)
references
References 26 publications
2
78
0
2
Order By: Relevance
“…Moreover, as compared to polymeric materials, carbonized membranes have higher tolerance to harsh environments due to the sluggish chemical reactivity and better thermal resistance. The microstructure of carbon membranes from polyimides is determined by a number of factors including: (1) the different chemical structure of polyimides which induces dissimilar chain packing, thermal stability, molecular flatness and in-plane orientation [27,28]; (2) the pyrolysis conditions such as temperature, atmosphere and heating rate [29,30]; (3) the pre-treatment of polyimide before carbonization using thermostabilization, polymer blending, nonsolvent immersion or chemically grafted side groups [31][32][33][34][35][36][37]; (4) post-treatment of carbonized membranes by oxidation or chemical vapor deposition [38][39][40].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, as compared to polymeric materials, carbonized membranes have higher tolerance to harsh environments due to the sluggish chemical reactivity and better thermal resistance. The microstructure of carbon membranes from polyimides is determined by a number of factors including: (1) the different chemical structure of polyimides which induces dissimilar chain packing, thermal stability, molecular flatness and in-plane orientation [27,28]; (2) the pyrolysis conditions such as temperature, atmosphere and heating rate [29,30]; (3) the pre-treatment of polyimide before carbonization using thermostabilization, polymer blending, nonsolvent immersion or chemically grafted side groups [31][32][33][34][35][36][37]; (4) post-treatment of carbonized membranes by oxidation or chemical vapor deposition [38][39][40].…”
Section: Introductionmentioning
confidence: 99%
“…CMSMs compare favorably with their polymer precursors by exhibiting intensive gas transport properties. It can achieve higher selectivity without loosing the productivity [2][3][4][5][6][7][8][9] and thus surpass the upper bound limit of polymeric membranes. CMSMs have also been recognized with advantages of higher thermal and chemical stability [2,[9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have reported that a CMSM with tailored microstructure (pore size, pore volume, etc.) could be obtained by controlling the pyrolysis conditions [2,6,9,13,15,[17][18][19] and post-/pre-treatment conditions [7,10,[20][21][22][23][24]. On the other hand, CMSMs can be modified to improve their permeation properties or to solve several problems inherent to their structures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…So far, microporous silica membranes have been prepared by sol-gel (Asaeda and Kitao, 1991) and CVD (Tsapatsis et al, 1991) techniques. Further, microporous carbon membranes have been prepared by the carbonization of various types of precursors such as phenol resin (Kita et al, 1997;Centeno and Fuertes, 1999;Fuertes, 2001;Zhou et al, 2001), polyfurfuryl alcohol (Shiflett and Foley, 2001) and polyimide resin (Jones and Koros, 1994;Haraya, 1995, 1997;Hayashi et al, 1997;Peterson et al, 1997;Fuertes and Centeno, 1998;Okamoto et al, 1999). These membranes showed higher selectivity than organic polymer membranes (Nakagawa, 1985) for the gas separations mentioned above.…”
Section: Introductionmentioning
confidence: 99%